Strategic HR Planning and Human Capital Investment in Improving Employee Performance: Mediation of Employee Engagement and Moderation of Psychological Safety - Paroli (PT Inovasi Pratama Internasional, 2026)
Changes in the work environment and demands for improved employee performance have made human resource management an increasingly important strategic factor, including in religious-based educational institutions. Organisations not only need targeted HR planning, but also investment in human capital development and a work environment that supports employee engagement. This study aims to analyse the effect of Strategic Human Resource Planning and Human Capital Investment on Employee Performance with Employee Engagement as a mediating variable and Psychological Safety as a moderating variable. This study uses a quantitative approach with explanatory research. The research population consists of all employees and educators at the Inspiratif Al Ilham Islamic Boarding School in Bojongsoang, West Java. The sampling technique used simple random sampling with a sample size of 100 respondents. Data were collected through questionnaires and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) through SmartPLS. The results showed that human capital investment and strategic human resource planning played a role in increasing employee engagement, which in turn drove performance improvement. Psychological safety was also found to strengthen the relationship between engagement and performance, enabling employees to work more optimally in a psychologically safe environment. This study implies that educational institutions need to strengthen human resource investment, build work engagement, and create a supportive work climate to improve employee performance in a sustainable manner.